Discurso de mães doadoras : motivos e sentimentos subjacentes à doação - Menezes, Karla Fabiana Figueiredo Luna de (2007)
This work aimed at understanding the motives and feelings that underlie the speech of biological mothers who give away their children as well as the consequences of such act in their lives. Psychological attendance to those mothers, still in the maternity ward, reveal a rationalization of such a motive, making it implicit something supposed to belong to the area of desire. Six mothers between the ages of 22 and 40 years old were interviewed. They presented low education and low social-economic levels and gave away two children at least. Children ages varied between 0 to 3 years old. A semi-structured interview was conducted with each mother comprehending social-demographic data and questions that met the objectives of this research. Verbal and non-verbal contents of genitors discourse under a psychoanalyst perspective were analyzed with the aim of identifying possible motives and feelings related to the act of giving away a child. It was verified that the mothers presented poor material and emotional conditions that permeate their lives hindering them from having a balanced emotional development that would enable them to be mothers. Their childhood was characterized by hardships, violence, needs, incomprehension and abandonment. Their social-economic and family context during pregnancy was unfavorable to a psychological balance, adding to that premature pregnancy. It was found that the main cause for giving away a child was immaturity together with the lack of family support and absence of the child´s father as well as social-economic difficulties. The feelings experienced by the mother after giving away their children, are guilty, sadness, anguish, grief and repentance. Feelings of insufficiency or incapacity were also found to be unconscious motivators to the act of giving away. In relation to the impact of the act of giving away in the mothers lives, it was found that even after wondering about re-starting a new life after giving away a child, all of them appeared to be bitter, tired, dissatisfied and unhappy. It is concluded with this work that the motives for giving away a child is contextual and individual depending on social factors and much more on intra-psychological factors. It is a complex subject, impossible to be generalized. The particularity of each case should be carefully studied as well as the factors underlying them.